Mismatch in the graduate labour market among immigrants and second-generation ethnic minority groups - Delma Byrne; Seamus McGuinness (The Economic and Social Research Institute (ESRI), 2009)
This paper uses graduate survey data and econometric methods to estimate the incidence and wage effects of over-education and overskilling among immigrant and ethnic minority graduates from UK universities. The paper empirically demonstrates that immigrant and second-generation ethnic minority graduates were no more likely to experience education or skill mismatch relative to their native counterparts. Furthermore, graduates from immigrant and ethnic minority backgrounds incurred overeducation and overskilling wage penalties that lie well below the level incurred by native graduates. The research stresses the importance of controlling for the effects of location-specific human capital and sample selection when undertaking studies of this nature.
Keywords: J21; J31; J61; 330; overeducation; overskilling; ethnic minorities; immigrants; Ethnische Gruppe; Migranten; Unterbeschäftigung; Akademiker; Einkommen; Vergleich; Bevölkerung; Großbritannien